DELTA2 guidance on choosing the target difference and undertaking and reporting the sample size calculation for a randomised controlled trial. (5th November 2018) - Cook, Jonathan A; Julious, Steven A; Sones, William; Hampson, Lisa V; Hewitt, Catherine; Berlin, Jesse A; Ashby, Deborah; Emsley, Richard; Fergusson, Dean A; Walters, Stephen J; Wilson, Edward C F; MacLennan, Graeme; et al.
Abstract : Randomised controlled trials are considered to be the best method to assess comparative clinical efficacy and effectiveness, and can be a key source of data for estimating cost effectiveness. Central to the design of a randomised controlled trial is an a priori sample size calculation, which ensures that the study has a high probability of achieving its prespecified main objective. Beyond pure statistical or scientific concerns, it is ethically imperative that an appropriate number of study participants be recruited, to avoid imposing the burdens of a clinical trial on more patients than necessary. The scientific concern is satisfied and the ethical imperative is further addressed by the specification of a target difference between treatments that is considered realistic or important by one or more key stakeholder groups. The sample size calculation ensures that the trial will have the required statistical power to identify whether a difference of a particular magnitude exists. In this article, the key messages from the DELTA 2 guidance on determining the target difference and sample size calculation for a randomised controlled trial are presented. Recommendations for the subsequent reporting of the sample size calculation are also provided.